Assessing the Speaking Skill: A Study in the Third Level Education - Mauriza Hesti Nurkhofifah; Annisa Juliani; Ully Manik; Yudi Juniardi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2023)
The aim of this study is to get deeper into the concept and process of speaking assessment. The assessment has a significant impact on students' learning because it plays a vital role in fostering students’ speaking capability in the learning process. Evaluating and assessing students' achievement in the learning process can give the direct impact toward students learning directly. This study focuses on the speaking assessment at the higher education level, what is the purpose of the speaking assessment, the technique and tools that is used in the assessment. The method used in this study is library research method, by collecting and identifying factual data from various sources and experts’ opinions. Researchers found from the study the purpose of speaking skill assessment is to measure the learning impact. Some techniques in conducting speaking assessment are: public speaking assessment, short and answer assessment, peer-assessment, self-assessment, direct, semi-direct, and indirect assessment, and digital formative assessment and the dynamic assessment for both direct and online or technology basis. The tools in conducting the speaking skills assessment are holistic rubric, analytical rubric, computer-based oral exams.